In search of Islamic principles for urban environmental design - Mohit, Mohammad Abdul (2008)
Urban Environmental Design (UED)' is basically concerned with the concepts, theories, and principles of designing space for various human activities in urban areas. It encompasses all the creative and professional fields that are related to the making of human habitations and its integration with nature. The conventional approach of UED is primarily based on the market principles, I.e., price and value as the prime indicators. It is viewed that the elements of planning in the urban built environment can be pursued through the adoption of principles derived from the revealed knowledge of al-Qur'an which is treated as a source of human knowledge for human benefit. It is possible to develop Islamic principles based on which the resources of the world can be better utilized for the maximum benefit of mankind. There are strong traditions within Islam about urban environmental design. The various activities of urban built environment or environmental design are associated with the management of resources such as land and all its environmental and physiographical features, making it beneficial for mankind (Ismawi Hj. Zen, 2002, p.2).